A Worm's World: Ecological Flexibility Pays Off for Free-Living Nematodes in Sediments and Soils. (4th September 2019) - Schratzberger, Michaela; Holterman, Martijn; van Oevelen, Dick; Helder, Johannes
Abstract: Free-living nematodes, an ancient animal phylum of unsegmented microscopic roundworms, have successfully adapted to nearly every ecosystem on Earth: from marine and freshwater to land, from the polar regions to the tropics, and from the mountains to the ocean depths. They are globally the most abundant animals in sediments and soils. In the present article, we identify the factors that collectively explain the successful ecological proliferation of free-living nematodes and demonstrate the impact they have on vital sediment and soil processes. The ecological success of nematodes is strongly linked to their ability to feed on various food sources that are present in both sediments and soils, and to proliferate rapidly and survive in contrasting environmental conditions. The adaptations, roles, and behaviors of free-living nematodes have important implications for the resilience of sediments and soils, and for emergent animal communities responding to human alterations to ecosystems worldwide.